Implementing TOGAF ADM for Enterprise Architecture Development and Governance: Evidence from a Large-Scale Technology Enterprise - Salwa Nabilah Assidiq; Muh Anugerah Jufri; Hajar Dewantara; Betania Kartika Muflih (Indonesian Journal of Enterprise Architecture, 2025)
Enterprise architecture (EA) is a structured approach to designing, developing, and managing information technology (IT) infrastructure to support business objectives. TOGAF is a popular enterprise architecture framework and is widely used by large enterprises to develop and manage their IT architecture. This article discusses the implementation of TOGAF at IBM and explains how the company managed to develop a structured and well-coordinated enterprise architecture. IBM Enterprise has implemented TOGAF as the main framework in developing and managing their IT architecture. They use TOGAF as a tool to integrate their IT architecture with business needs and to ensure that the IT solutions developed can meet their business and technology requirements. In implementing TOGAF, IBM follows a set of well-documented processes and practices. They started by identifying their business architecture and designing the right IT architecture to support their business goals. The result of the TOGAF implementation at the IBM company is the development of a structured and well-coordinated enterprise architecture. In addition, IBM can manage risk more effectively and ensure that their IT architecture aligns with their business strategy.